Socialism and its culture - Bukharin, Nikolai (London, 2006)
Bukharin's "Prison Manuscripts" were written in Moscow's Lubyanka prison during 1937-1938 while awaiting his inevitable liquidation. As with Gramsci's "Prison Notebooks", Bukharin's "Manuscripts" focus on culture, ideology and philosophy in the context of building an alternative vision of socialism. A socialism to set against capitalism, fascism and the kind of socialism practised in the Soviet Union after Lenin's death. The book brings together Bukharin's key writings on socialism and its culture from the Manuscripts. Here Bukharin explores the realization of the concept of total man, the problems of freedom, equality and hierarchy, the style of socialist culture, the nature of progress, diversities in capitalism and socialism, the role of the Party, and the dictatorship of the proletariat in the cultural revolution. Its publication will be a major event for anyone interested in cultural and political history, philosophy, and ethics.
Keywords: Socialism